The Impact of the Covid-19 Pandemic on Language and Social Development for Early Childhood Children age 4-6 years in Karawang District - Darmiyanti, Astuti; Supriadi, Oding; Nurlaeli, Acep (Universitas Negeri Semarang, 2021)
Children in early age are unique people, where they have a pattern of growth and development. Language development reflects the growth and learning process of the children and it depends on maturity and learning opportunities. In early childhood education, there are 4 development aspects as a reference in stimulation for development and early childhood growth, which is language and social emotional aspects, cognitive and psychomotor. COVID-19 pandemic has shifted the process of early childhood education, which includes assessing early childhood development from teachers to parents at home. This study endeavours to understand how much COVID-19 pandemic will impact the growth and development of 4-6 years old children, especially the language and social emotional aspects during online learning in the midst of the COVID-19 pandemic. The result indicates the impact of COVID-19 pandemic with School From Home (SFH) policy shows that there are groups of respondents who are still having difficulty achieving the set of curriculum targets by the government, and it could affect the development and growth of children's language skills and social emotionality. The population in this study were teachers and parents of Islamic Early Childhood (RA or PIAUD) and Early Childhood students (PAUD) in Karawang Regency, Indonesia, and the sample size would be determined using the Slovin formula with an error tolerance limit of 5% (0.05). This study collects the data using a questionnaire and interviews.